The review : International Commission of Jurists - International Commission of Jurists (1952- ) (The Commission, 1952)
Current frequency: 2/year.Merger of: Bulletin of the International Commission of Jurists; Journal of the International Commission of Jurists; CIJL yearbook;Yearbook of the International Commission of Jurists.